Competitiveness and bound tariff requirements of Indian agricultural commodities - Naik , Gopal; Naik, Gopal; Indian Institute of Management, Ahmedabad. Centre for Management in Agriculture (New Delhi : Oxford & IBH Pub. Co., 2004)
Study conducted by Centre for Management in Agriculture, Indian Institute of Management, Ahmedabad.
Includes bibliographical references (p. 175).
Keywords: World Trade Organization; Tariff on farm produce -- India; Competition, International; Agriculture -- Economic aspects -- India